Analisis Validitas dan Kekuatan Pembuktian Akta Otentik dalam Transaksi Jual Beli Tanah Berdasarkan Hukum Indonesia - Salsabila Ghina Luthfiyah; Siti Malikhatun Badriyah (Jurnal Hukum Lex Generalis, 2025)
The role of notaries in ensuring the validity of authentic deeds in land sale transactions is crucial in Indonesia’s civil law system. Notaries are tasked with ensuring that these transactions are legally valid, comply with all requirements stipulated by the Civil Code (KUHPerdata), and possess strong evidentiary power in court. A key aspect of this role is to ensure that the parties have the legal capacity to engage in the transaction and that the land being sold has a clear legal status, such as a certificate registered with the National Land Agency (BPN). The validity of the notarial deed is also influenced by factors such as incomplete documentation, unclear legal status of the parties involved, and non-compliance with applicable regulations. To address these issues, notaries must ensure proper document verification and provide adequate explanation to the parties about their rights and obligations. Legal solutions to these problems include verifying the legal status of the land, fulfilling tax obligations, and preventing fraudulent actions in the transaction. Therefore, notaries act not only as witnesses but also as protectors of legal certainty in land sale transactions.